2021
DOI: 10.1002/int.22493
|View full text |Cite
|
Sign up to set email alerts
|

Digital‐twin assisted: Fault diagnosis using deep transfer learning for machining tool condition

Abstract: The rapid development forms a new transition of information technologies to offer an intelligent manufacturing. The manufacturer has revolutionized the stages of product lifecycle including process planning and maintenance for the early detection of potential system failures and proactive management. Technological advancements including big data, the cloud, and the Internet of Things have applied digital‐twin for industrial practice. It has low‐power wireless‐enabled devices to play a vital role in various ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Luo et al [100,172,173] established a multi-domain unified modeling approach for digital twins, explored the mapping strategy between physical and digital spaces, and proposed a self-prediction and self-maintenance method for digital twins. If machine tools can be built with a digital twin in virtual space that can monitor the health status and operating history of machine tools at any time, unnecessary losses caused by unexpected events can be greatly avoided [101,[174][175][176][177]. Scaglioni et al [98] developed a dynamic model of the Mandelli M5 machine tool.…”
Section: The Applicationsmentioning
confidence: 99%
“…Luo et al [100,172,173] established a multi-domain unified modeling approach for digital twins, explored the mapping strategy between physical and digital spaces, and proposed a self-prediction and self-maintenance method for digital twins. If machine tools can be built with a digital twin in virtual space that can monitor the health status and operating history of machine tools at any time, unnecessary losses caused by unexpected events can be greatly avoided [101,[174][175][176][177]. Scaglioni et al [98] developed a dynamic model of the Mandelli M5 machine tool.…”
Section: The Applicationsmentioning
confidence: 99%
“…Accurate models aren't always available for the system of which we want to build a DT for its operating conditions. The problem of the availability of data could possibly be solved using Generative Adversarial Networks (GANs) [18][19][20] and/or transfer learning [21][22][23][24][25], but the technology is still maturing. For this study, General Additive Models (GAMs) are used as they are a category of ML that requires few to none hyperparameters tuning to approximates nonlinear relationships with a combination of linear formulation of a series of smoothening functions [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the service stage, DT can diagnosis and predict equipment faults based on real-time status data. Based on deep transfer learning algorithm to realize digital twin-assist fault diagnosis for analyzing the operating status of machine tools [20]. Xiong et al [21] proposed a digital twin-driven predictive maintenance framework that combined a datadriven with LSTM model to perform predictive maintenance on aero-engine, and the experimental results showed that the method had high predictive accuracy.…”
Section: Related Work a Digital Twin In Manufacturingmentioning
confidence: 99%